Efektivitas Pelayanan Partisipatif Tim Pamsimas (Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat) Dalam Pendistribusian Air Bersih di Desa Bakti Makmur - Nurkholizah, Siti; Saputra, Agung (Universitas Muhammadiyah Sumatera Utara, 2024)
The Pamsimas III program is expected to provide access to clean water to the community and in accordance with the targets and objectives of the Pamsimas program with the formation of the Pamsimas team. This research aims to analyze the services of the Pamsimas team in distributing clean water using a pipe network that is distributed to each community's house. This researcher used descriptive research methods with qualitative analysis. Descriptive research methods emphasize observational research in the field, interviews, and also data or documents. The data sources used in this research are secondary data and primary data with a total of 11 key informants, including the Pamsimas team, the Head of Bakti Makmur Village, the RT, and the local community. The results of this research show that the Pamsimas program carried out by the Pamsimas team in Bakti Makmur Village, Bagan Sinembah Raya District, Rokan Hilir Regency has been running effectively. Judging from the implementation of the program according to the objectives, the services provided by the Pamsimas team, even though the target is not 100% correct, many people who have experienced the impact have felt the benefits of the program. The effectiveness of the Pamsimas team's services in distributing clean water is seen from 7 indicators, namely: transparency, accountability, participatory, equal rights, facilities, availability of goods and services, and selection of distribution channels. Of the seven indicators, only participation is lacking because the community does not participate fairly in the Pamsimas program, only relying on the Pamsimas team.